Caracterização de culturas 3D de cardiomiócitos em substratos formados por nanofibras de acetato de celulose associadas ou não ao urucum - Ana Elisa Antunes dos Santos (2020)
Myocardial infarction is one of the leading causes of death worldwide. The clinical result, in some cases, is the replacement of native tissue with scar tissue leading to loss of function at that location. Tissue engineering applies the principles of materials engineering and life sciences to the production of biological substitutes in regenerative medicine, among others. The development of cardiac tissue engineering may lead to the production of biological substitutes capable of restoring the function of the damaged myocardium. The creation of bioactive scaffolds, which are three-dimensional matrices capable of allowing cell adhesion, migration, proliferation and differentiation, allowed three-dimensional cell culture for the production of organs and tissues in various types of matrices. Cellulose acetate nanofibers are an excellent option for use as scaffolds, due to their biocompatibility and low cost. Nanofibers mimic the native extracellular matrix, allow the regulation of mechanical properties and have a large surface area, enabling better adhesion and cell proliferation. In order to optimize the cellulose acetate nanofibers, bixin, a bioactive molecule derived from annatto seed, was incorporated. In this sense, we intend to test the cell culture of lineage and primary cardiomyocytes in cellulose acetate nanofibers functionalized or not with crude annatto extract, which would be the first step towards the production of a cardiac substitute. Through in vitro analyzes it was possible to demonstrate that cellulose acetate nanofiber membranes incorporated or not to annatto showed biocompatibility with H9c2 cells, cardiac myoblasts, favoring cell adhesion and viability. In addition, the H9c2 cells cultured in the nanofibers showed morphology similar to cardiac myocytes in a proliferative medium. Furthermore, when differentiation was induced, these cells did not change in shape, which could indicate a differentiation process in these matrices without the need to induce differentiation. Finally, cellulose acetate nanofiber membranes incorporated or not into annatto proved to be a good matrix for the culture of primary cardiomyocytes.